Analisis Pengendalian Manajemen terhadap Pengelolaan Arus Kas pada PT Global Bangunan Seraya - Christian, Natalis; Angelin, Angelin (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
This Community Service Program (PkM) was implemented to address PT Global Bangunan Seraya's main issues, including unstable cash flow, debit bottlenecks, lack of standardized financial SOPs, and limited staff understanding of management control. Methods used included interviews, observations, documentation studies, literature studies, module development, SOP development, financial report template development, training, and mentoring. This program produced five implementable outcomes. Results showed improvements in staff abilities to analyze cash flow, transaction recording accuracy, and consistent use of standard financial reports (cash flow statements, profit and loss, and balance sheets). Internal control discipline improved through SOP implementation and evaluations, enabling regular company monitoring and corrections. This discipline created a more orderly, transparent, and stable cash flow management system for the company. Future recommendations include deeper coverage of long-term financial projections, measuring reductions in Days Sales Outstanding (DSO), developing digital financial dashboards, and ongoing training to strengthen the company's financial management capacity.